Meta-Analysis: Factors Related with Premarital Sexual Behavior in Adolescents - Aktif Cahyaning Tyas; Hallisa'tu Zahro; Putri Fortuna Salsabila; Aem Ismail; Bhisma Murti (Journal of Health Promotion and Behavior, 2024)
Background: Premarital sexual behavior is a sexual activity carried out before marriage. Premarital sexual behavior is a health priority in adolescents because it causes unwanted pregnancies, abortions, STIs, HIV/AIDS and even death. Parents, peers, community environment, economic and cultural conditions influence premarital sexual behavior. This study aims to analyze the effect of peers, smoking behavior, alcohol consumption, exposure to pornography and rural areas on premarital sexual behavior in adolescents. Subjects and Method: This was a systematic review and meta-analysis of study articles. Data obtained from databases including Google Schoolar, Pubmed and Science Direct. Article search was carried out by considering eligibility criteria with the PICO model. Population: adolescents. Intervention: high peer pressure, smoking behavior, alcohol consumption, exposure to pornography, and rural areas. Comparation: low peer pressure, non-smoking, no alcohol consumption, no exposure to pornography, and urban areas. Outcome: premarital sexual behavior. The articles were collected with keywords including "Peer Pressure" AND "Smoking" AND "Alcohol Compsumtion" AND "Pornography Exposure" AND "Rural" OR "Premarital Sexual Behavior" AND "Cross Sectional Study". Study articles were collected with PRISMA flow diagrams and analyzed using Review Manager 5.3 application. Results: The results of the meta-analysis indicated that adolescents were influenced by premarital sexual behavior in the presence of high peer pressure (aOR= 3.57; CI95%= 1.38 to 9.26; p<0.001), smoking behavior (aOR= 1.17; CI95%= 0.63 to 2.16; p<0.001), alcohol consumption (aOR=2.11; CI95%=1.34 to 3.33; p<0.001), and exposure to pornography (aOR= 2.43; CI95%= 1.44 to 4.09; p<0.001). Conclusion: Adolescent premarital sexual behavior increases with high peer pressure, smoking, alcohol consumption, and exposure to pornography.